Post‐Keynesian Economics: A User's Guide. (September 2015) - Hart, Neil; Kriesler, Peter
Abstract This article provides a brief introduction to post‐Keynesian economics. Post‐Keynesians are sceptical of the usefulness of the equilibrium method and favour an approach based on path‐determined models with, due to the influence of uncertainty on economic decisions, an important role assigned to money, institutions and rules of thumb. As there are no forces within capitalist economies which can guarantee full employment, government intervention is important. While monetary policy is seen as a rather blunt instrument, fiscal policy is perceived to be much more potent than it is in the mainstream. However, there are inherent limits to the achievement of sustained full employment in capitalist economies.